Comparison of nanocomposite colour particle stability after immersion in black tea and green tea - Pramudiyanti, Nindya; Febrida, Renny; Usri, Kosterman (Universitas Padjadjaran, 2015)
Introduction: Restorations using composite resins have to meet several requirements, one of which is stable against discoloration. Unfortunately discoloration may happen to this kind of restoration, and one of the causes is the tea habit. This research was to compare the color stability of nano particle composite after soaked in black tea and green tea. Methods: The research method was a laboratory experiment using nano particle composite as samples. It was conducted to 15 samples in cylindrical shape with diameter of 7 mm and thickness of 2 mm. Samples were divided in to 3 groups, each group consists of 5 samples. The first group soaked in black tea, the second group soaked in green tea and the last one soaked in mineral water for 7 days. Color measurements were obtained by using spectrophotometer (CIE lab system) and color differences (∆E) were estimated. For statistical evaluation, analysis of variance (ANOVA) was used with 5% error level. Results: There are differences in color stability of nano composite after soaked in black tea and green tea. The value of color differences after soaked in black tea is 2,669 and green tea is 3,062. Conclusion: The stability of nano particle composite color is better at soaking with black tea compared with immersion with green tea.